Spatial Analysis and Quantitative Microbial Risk Assessment (QMRA) on The Quality of Refilled Drinking Water in Puskesmas Work Area Moncongloe Maros District - Ahmad, Ibrahim (Manunggal Halim Jaya, 2021)
The type of research used is descriptive research with a Microbial Risk Assessment (MRA) on refilled drinking water (Ryan et al., 2022). The design of this study uses a Geographic Information System (GIS) approach. Retrieval of data using the exploratory method, namely sampling is done directly. The research was carried out in the Working Area of the Moncongloe Health Center, Maros Regency, for approximately 1 (one) month in October 2020. The population in this study were all Refill Drinking Water Depots in the working area of the Moncongloe Health Center, Maros Regency, namely 17 depots. The sampling technique in this study was total sampling, namely 17 Refill Drinking Water Depots in the working area of the Moncongloe Health Center, Maros Regency. The bacteria that became the research were Escherichia coli bacteria. The exposure assessment was carried out on 170 respondents, namely 10 respondents who consumed drinking water from each depot. The type of data used in this study is quantitative data in the form of the results of laboratory examinations for Escherichia coli content in refilled drinking water.